Front Cover: Angular Trapping of Spherical Janus Particles (Small Methods 12/2020). Issue 12 (3rd December 2020) - Gao, Xiaoqing; Wang, Yali; He, Xuehao; Xu, Mengjun; Zhu, Jintao; Hu, Xiaodong; Hu, Xiaotang; Li, Hongbin; Hu, Chunguang
Abstract : In article number 2000565, Hongbin Li, Chunguang Hu, and co‐workers develop a novel angular trapping method based on composite Janus particles. Using this easy‐to‐implement method, the Janus particle can be rotated in the laser trap in a fully controlled fashion in real time.